A combination of ballistic exercises with slow and fast stretch-shortening cycle induces post-activation performance enhancement - Kumar Thapa, Rohit; Kumar, Amar; Kumar, Gopal; Narvariya, Pushpendra (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The stretch-shortening cycle (SSC) ability of a muscle is responsible for sprinting and changing direction during sports activity. Sprinting involves more fast SSC ability while a change of direction (COD) requires both fast and slow SSC. Post-activation performance enhancement (PAPE) is an acute enhancement of muscular performance due to previous muscular contraction. Heavy resistance exercises and plyometric exercises are commonly used PAPE method, utilizing either slow or fast SSC activity for inducing PAPE. Aim of Study. This study aimed to examine the effect of a combination of ballistic exercises (BE) with slow and fast SSC on sprint and COD ability. Material and Methods. In a randomized crossover manner, 12 male university basketball players (age 21 ± 1.2 years; height 170 ± 8 cm; body mass 66.8 ± 7 kg; fat percentage (%) 10.2 ± 2.4) performed 3 × 5 repetitions of a combination of box jump and immediate drop jump (BDJ) or walking control after a standard warm-up protocol. A baseline measurement was recorded 1 minute after warm-up and post-measurement after 3 minutes of interventions. Results. Significant large improvement in COD performance was observed after BDJ compared to baseline (p < 0.001, d = 0.982) and controlled conditions (interaction effect; p = 0.006, partial η2 = 0.518). While, no improvement was found in 15 m sprint performance with baseline (p = 0.282, d = 0.285) or controlled conditions (interaction effect; p = 0.649, partial η2 = 0.020). Conclusions. The results of the study suggest that warm-up followed by a BDJ protocol induces PAPE effect and improves COD performance.
Keywords: modified agility T-test; 15 m sprint; BDJ; box jump; drop jump; SSC